2023
DOI: 10.3389/fendo.2023.1185799
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning immune-related gene based on KLRB1 model for predicting the prognosis and immune cell infiltration of breast cancer

Abstract: ObjectiveBreast cancer is a prevalent malignancy that predominantly affects women. The development and progression of this disease are strongly influenced by the tumor microenvironment and immune infiltration. Therefore, investigating immune-related genes associated with breast cancer prognosis is a crucial approach to enhance the diagnosis and treatment of breast cancer.MethodsWe analyzed data from the TCGA database to determine the proportion of invasive immune cells, immune components, and matrix components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In the initial stage of tumor colonization or growth, the TME hinders the occurrence and development of tumors ( 24 ). However, the continuous stimulation of tumor antigens and immune activation responses results in the exhaustion or remodeling of the related effector cells in the TME, rendering them unable to perform physiological functions or promoting the malignant manifestations of tumors ( 25 ). The immune, stromal, and estimate scores were analyzed to evaluate the immune status of the three clusters.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial stage of tumor colonization or growth, the TME hinders the occurrence and development of tumors ( 24 ). However, the continuous stimulation of tumor antigens and immune activation responses results in the exhaustion or remodeling of the related effector cells in the TME, rendering them unable to perform physiological functions or promoting the malignant manifestations of tumors ( 25 ). The immune, stromal, and estimate scores were analyzed to evaluate the immune status of the three clusters.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 31 ] KLRB1 is a possible prognostic marker and therapeutic target linked with human esophageal squamous cell carcinoma [ 17 ] and breast cancer tumors. [ 32 ] In this study, we examined the expression of KLRB1 in diverse pathological types of TGCTs by analyzing mRNA sequence data from 134 TGCTs patients in the TCGA database. In our study, we showed that KLRB1 was upregulated in tumor tissues, especially in seminomas, and that elevated KLRB1 expression correlated with adverse clinicopathological features of TGCT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SPARC secreted by CAFs promotes tumor growth by inhibiting adhesion of triple-negative BC cells whilst stimulating invasion and metastasis [19]. Recently, KLRB1 has become an increasing focus in tumor research as it has been associated with tumor progression [11][12][13][14][15]20]. Xu and Huang et al found that KLRB1 is a tumor suppressor gene involved in the BC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that KLRB1 gene inactivation enhances T-cell-mediated killing of glioma cells in vitro and the anti-tumor function of KLRB1 in vivo [ 13 ], whereas decreased KLRB1 expression has been associated with poor prognosis in BC patients [ 11 ]. Xu and Huang et al found that KLRB1 is in the down-regulation trend in BC and a negative correlation between overexpression of KLRB1 and poor prognosis (such as overall survival (OS) and recurrence free survival (RFS)) of BC patients through survival analysis [ 14 , 15 ]. However, not much is known about the relationship between KLRB1 expression and BC subtypes (such as the BRCA) progression.…”
Section: Introductionmentioning
confidence: 99%